Postural control does not affect performing or learning a temporal estimation task in physically active older adults - Bastos, Flávio Henrique (Array, 2019)
Evidence suggests that postural control could act as a secondary task, leading to a negative effect on sensorimotor skill learning. To investigate this issue, twenty older adults (average age = 70.5 years, SD=5.6) were distributed into two groups, according to the body position maintained during the acquisition (AQ) of a temporal estimation task: performing the task standing with feet together (STA) or sitting (SIT). During the AQ, participants performed 90 trials of the task consisting of synchronising the arrival of two rectangles (‘Target A’ and ‘Target B’) to a target line. The velocity of Target A was chosen by the participants, among three possible ones, before each trial, without exceeding 30 trials per velocity. Target B had only one velocity and should be released by the participants, with a button press, when they judged it would reach the target line simultaneously with Target A. Contrary to what has been shown in studies with reaction time, postural control did not affect the performance of our temporal estimation task. Additionally, no effects on sensorimotor learning – inferred by immediate and delayed transfer tests – were found. Result suggests that postural control may not interfere with cognitive resources used to perform a simultaneous task, when this task does not demand fast processing, i.e. is not highly time constrained. Future studies should consider the physical activity level of participants, since the fact that all participants in the present study were physically active may have contributed to the observed results.